Loss of the ETR1 ethylene receptor reduces the inhibitory effect of far-red light and darkness on seed germination of Arabidopsis thaliana - Wilson, Rebecca L.; Bakshi, Arkadipta; Binder, Brad M. (Frontiers in Plant Science, 2014)
When exposed to far-red light followed by darkness, wild-type Arabidopsis thaliana seeds fail to germinate or germinate very poorly. We have previously shown that the ethylene receptor ETR1 (ETHYLENE RESPONSE1) inhibits and ETR2 stimulates seed germination of Arabidopsis during salt stress. This function of ETR1 requires the full-length receptor. These roles are independent of ethylene levels and sensitivity and are mainly mediated by a change in abscisic acid (ABA) sensitivity. In the current study we find that etr1-6 and etr1-7 loss-of-function mutant seeds germinate better than wild-type seeds after illumination with far-red light or when germinated in the dark indicating an inhibitory role for ETR1. Surprisingly, this function of ETR1 does not require the receiver domain. No differences between these mutants and wild-type are seen when germination proceeds after treatment with white, blue, green, or red light. Loss of any of the other four ethylene receptor isoforms has no measurable effect on germination after far-red light treatment. An analysis of the transcript abundance for genes encoding ABA and gibberellic acid (GA) metabolic enzymes indicates that etr1-6 mutants may produce more GA and less ABA than wild-type seeds after illumination with far-red light which correlates with the better germination of the mutants. Epistasis analysis suggests that ETR1 may genetically interact with the phytochromes (phy), PHYA and PHYB to control germination and growth. This study shows that of the five ethylene receptor isoforms in Arabidopsis, ETR1 has a unique role in modulating the effects of red and far-red light on plant growth and development.